2D modelling of pulsating stars with rapid rotation - Reese, Daniel Roy (Frontiers in Astronomy and Space Sciences, 2022)
Rapid stellar rotation is an important phenomenon in stellar physics, particularly for massive and intermediate mass main-sequence stars. This affects all aspects of the star’s physics including its structure, evolution, and pulsations, and makes it necessary to use 2D numerical approaches rather than the 1D approaches typically used. In this contribution, we will review 2D numerical methods for modelling and interpreting pulsation modes in rapidly rotating stars. We will start by deriving the pulsation equations, both in an adiabatic and non-adiabatic setting, then provide a description of the 2D numerical implementation. We will then explain approximate implementations of the effects of rotation, namely first, second, and third order perturbative approaches, as well as the traditional approximation. This will then be followed by a description on how to calculate disk-integrated mode visibilities in various photometric bands, and how to apply this to mode identification in rapid rotators. Finally, we will review some of the recent works that interpret the pulsation spectra of various stars as viewed in either a single photometric band or in multiple bands, and including supplementary constraints from interferometry and spectroscopy.